La diversidad cultural: literatura indígena en la biblioteca escolar - Apaza Espinoza, Silvia Patricia (2025)
This paper aims to identify how the State understands cultural diversity and how it is reflected in the literature present in textbooks. It asks, «How do the textbooks provided by the Ministry of Education represent cultural diversity?» Therefore, it seeks to correlate cultural diversity, indigenous literature, and school libraries. The first, cultural diversity, allows us to understand the existence of diverse ethnicities and communities; the second, indigenous literature, refers to the set of expressions of a singular word —written or oral— and is recognized by its literary forms (poetry, stories, etc.); and the school library is the space where the books are found. This research takes as its reference authors and texts that appear as part of the Ministry of Education’s resources for public educational institutions, so the focus is on library texts.